THE EFFECT OF TECHNOSTRESS ON STUDENTS' ACCEPTANCE OF DIGITAL CURRICULUM - Fitri Ramadhani Purnomo; Muthiah Fahria; Nayla Alvira Damayanti; Zahwa Praditha Eka Suci; Rizqi Surya Saputra; Santi Putriani (RADJA PUBLIKA, 2025)
This study explores the influence of technostress on digital curriculum acceptance among students at the Faculty of Economics and Business, Muhammadiyah University of Surakarta. Technostress, the psychological distress caused by difficulties adapting to technology, can hinder students' motivation and engagement in digital learning. A quantitative survey was conducted on 101 active students using platforms such as LMS, with data analyzed using SEM-PLS through Warp-PLS. The results showed that techno-overload (β = 0.207, p = 0.015) and techno-uncertainty (β = 0.460, p < 0.001) significantly influenced acceptance, while techno-invasion and techno-complexity were insignificant. Perceived usefulness and perceived ease of use were the main drivers of positive student attitudes, influenced by self-efficacy and institutional support. Interestingly, techno-overload encouraged adaptation despite causing stress. These findings emphasize the need for user-friendly digital curricula and digital literacy training to reduce technostress. This research provides insights for faculty to improve the effectiveness of digital learning through system design that supports psychological well-being and technology acceptance.